Evaluation of anxiety and depression in parents of children during COVID 19 pandemic and its association with knowledge, attitude, practice, socioeconomic status and screen time during COVID-19 pandemic: A cross-sectional study - Banoth Chaitanya; N. Shivaramakrishna Babji; B. G. Abhilash; Barathy Chandrasegaran (Journal of Clinical Sciences)
Background: Anxiety and depression among parents/caregivers during the COVID-19 pandemic largely influence their knowledge, awareness, and practice (KAP) regarding anti-COVID measures and their adherence to the personal protective measures for the prevention of infection. The present study was therefore done to evaluate the presence of anxiety and depression symptoms among parents during the COVID 19 pandemic and to find out its association with KAP and sociodemographic variables. Methods: This cross-sectional study was undertaken in the Department of Pediatrics of a tertiary care hospital from January to March 2021. Parents attending pediatric immunization clinics were interviewed on demographic data, screen time, socioeconomic status, knowledge, awareness, and practices about COVID-19. Probable anxiety and depression were assessed by the Hamilton scale and its association with KAP and sociodemographic characteristics was determined by Chi-square test or Fishers’ exact test. All tests were two-tailed with a significant P < 0.05. Results: Of 166 parents, 73.5% had probable anxiety, while 76.5% had probable depression. The knowledge, attitude, and practice components were good in 83.7%, 82.5%, and 29.5%, respectively. About 81.3% of parents had overall good to fair knowledge, awareness, and practice scores. Anxiety (P = 0.001) and depression symptoms (P < 0.0001) were significantly associated with KAP. Conclusion: The present study showed a good correlation of probable anxiety and depression among parents/caregivers of children with KAP, which impacted the preventive measures undertaken by them. Anxiety and depression symptoms were less in parents/caregivers with good KAP compared to caregivers with poor KAP.